POLITICAL CONFIGURATION AND THE DEVELOPMENT OF ISLAMIC ECONOMIC LAW IN INDONESIA DURING THE NEW ORDER AND REFORMATION ERA - Bambang Iswanto (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2021)
This article aims to comparatively view the political configuration in Indonesia in the New Order and the Reformation era related to the formation of law in Islamic economics. Recently, Islamic economics has become an issue that has attracted the interest of scholars and economic practitioners as it is the potential to become a large industry. Legal products and several policies were born as evidence of the development of Islamic economic law in Indonesia, such as the Halal Product Guarantee Act, the ratification of Government Regulations regarding the implementation of halal product guarantees, to the merger of conventional banks into shari'ah Banks. These phenomena show that the political configuration in the Reformation era is fertile ground for economic development. Then, what about the Political Configuration in the New Order era? This article is a legal study using historical and political approaches strengthened by legal political theories. The study found that there are different characteristics of Islamic economic law between authoritarian and democratic political configurations. This article emphasizes that the character of Islamic economic law in the New Order era tends to be orthodox; legal control was tightly held by the political elite and must be followed by the community (top-down). Meanwhile, the Reformation era brought the direction of Islamic economic law to responsive legal characteristics. The society holds legal control by making the elites as policymakers for the development of Islamic economic law (bottom-up).